IJCM_73A: Knowledge, attitude, practice, and perception of women regarding breastfeeding- A mixed method study conducted in the tribal areas of Koraput, India. - Bhakta Madhumita; Panda Jasmin Nilima; Satapathy Durga Madhab (Wolters Kluwer Medknow Publications, 2024)
Background: Breastfeeding is one of the most effective ways to ensure a child's health and survival. Contrary to WHO recommendations, fewer than half of infants under 6 months old are exclusively breastfed. Although we know about breastfeeding practices in urban and rural populations, very little knowledge is available about breastfeeding practices and their correlates among the tribal population. Objectives: 1. To assess the knowledge, attitude and practices prevailing among tribal women about breastfeeding 2. To explore the facilitators and barriers to infant breastfeeding practices amongst women in tribal areas. Methodology: Study design- Mixed method study. Study period- May, 2023 to July, 2023 Study population- tribal women of Koraput district. Study setting- villages in Koraput Inclusion criteria- 1. Women belonging to Scheduled Tribe communities. 2. Having at least one living issue. 3. Residing in their respective villages during the study period. Exclusion criteria- 1. Those who did not consent to the study. 2. Not residing in their respective villages. Sampling- Multistage sampling. Sample size- 500. Results: 78.6% of mothers belong to the age group 21-30 years, 93.4% were literate whereas 6.6% were illeterate, 88% were housewives with 78.8% belonging from joint family. Majority of them had good knowledge regarding breastfeeding, though they lacked clarity on the concept of exclusive breastfeeding. Majority of their knowledge about breastfeeding was from relatives or neighbours and healthcare workers. having multiple children in quick succession serves as a major barrier to exclusive breastfeeding. Conclusion: The findings can form targeted interventions and policy initiatives to reduce the barriers and promote the facilitating factors for optimal breastfeeding practices within this unique cultural setting, ultimately contributing to improved maternal and child health outcomes.